P PENGEMBANGAN GAME EDUKASI “PETUALANGAN ALJA” UNTUK MELATIH CONCEPTUAL UNDERSTANDING DAN PROCEDURAL FLUENCY SISWA SMP MATERI ALJABAR: pengembangan game edukasi mateei aljabar - Wicaksono, Gesit (Satya Widya, 2021)
Games are one of the entertainments that are often and in demand by many children, especially those that can be used in electronic media. The educational game media developed in this research is "Petualangan Alja" which includes algebraic material. Addie model is used in research research and development (R&D) and there are 5 stages of development, namely: analysis, design, development, implementation, and evaluation. This educational game has confirmed its validity as a learning medium by materials and media experts with 95% and 95% results obtained. 5 students of grade 7 of SMP Negeri 1 Getasan and SMP Negeri 6 Salatiga were selected as research subjects. The results showed that the percentage of practicality obtained was 94.7% with a very good category. The significance result of the Paired T-Test test was 0.039 which was less than 0.05 with the learner's learning outcomes increasing significantly from the higher posttest average score of the pretest score. The conclusion of this study is that the educational game "Petualangan Alja" is valid, practical, and effective.